Human tail in a newborn - Josue Rueda (Elsevier, 2022)
Human tails are extremely infrequent and are generally diagnosed after birth, with no antenatal or family history associated with its occurrence. Different classification systems exist, however given its association with spinal dysraphism, it is important to include imaging studies during the assessment of patients with this congenital anomaly. We present the case of a human tail with no underlying spinal dysraphism that successfully underwent simple resection and reconstruction with Limberg plasty.